1216. An Outbreak Investigation of Pulmonary Infections Caused by Mycobacterium abscessus in a Cardiothoracic Transplant Population. (15th December 2022) - Rathod, Shardul N; Weber, Rachel; Salim, Asra; Tanna, Sajal D; Stosor, Valentina; Malczynski, Michael; Chao, Qi; Angarone, Michael P; Ison, Michael G; Williams, Janna L; Zembower, Teresa; Bolon, Maureen K
Abstract: Background: Nontuberculous mycobacteria (NTM) are environmental organisms that can form biofilms in municipal water systems and as such are difficult to eliminate. Mycobacterium abscessus is a rapid-growing NTM that can cause skin and soft tissue, disseminated, and pulmonary infections. M. abscessus is difficult to treat, often requiring prolonged therapy with several antibiotics due to its intrinsic drug resistance. In 2021, our institution identified a significant increase in pulmonary infections caused by M. abscessus in the cardiothoracic transplant population. Methods: All M. abscessus cases among inpatients at our institution were extracted from the electronic medical record (EMR) between January 2019 and September 2021. Clinical characteristics were determined through EMR review and included demographics, transplant status, specimen type, COVID-19 history, and patient care practices involving water. A multidisciplinary team conducted an investigation to identify possible variations in practice related to the source of water used for clinical care activities in this identified population. Results: Between January 2021 and September 2021, there were 12 cases of M. abscessus among inpatients at our institution compared to 6 cases in 2019 and 5 in 2020 (Figure 1). Between 2019 and 2020, post-heart and pre-/post-lung transplant patients comprised 9% of cases, 55% of cases were pulmonary infections, and none had a history of COVID-19 infection. In 2021, post-heart and pre-/post-lung transplant patients comprised 58% of cases, 83% of cases were pulmonary infections, and 33% of cases had a history of COVID-19 infection. There were varying sources of water utilized for the clinical care activities in this identified population (Table 1). Figure 1 Mycobacterium abscessus epidemic curve Table 1 Patient Care Practices Involving Water Conclusion: To investigate the potential outbreak, we are actively collecting water samples and swabs from water fixtures in both patient and nourishment rooms for water culturing. To mitigate a potential water-borne source, we will use sterile water for all clinical care practices involving water and for all patient water drinking needs in the post-heart and pre-/post-lung transplant population impacted by the outbreak. The only use of tap water is hand hygiene and patient bathing. Disclosures: Asra Salim, MPH, CPH, FAPIC, IRhythym Technologies Inc: Stocks/Bonds Valentina Stosor, MD, DiaSorin: Advisor/Consultant|Eli Lilly and Company: Grant/Research Support|Med Learning Group: Honoraria Michael P. Angarone, DO, Abbvie: Advisor/Consultant Michael G. Ison, MD MS, GlaxoSmithKlein: Grant/Research Support|Pulmocide: Grant/Research Support|Viracor Eurfins: Advisor/Consultant Janna L. Williams, MD, Abbvie: COVID19 Infection Prevention Consultant.